CLOUD COMPUTING: TRANSFORMING THE DIGITAL LANDSCAPE - Venkata Reddy Keesara (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
Cloud computing has fundamentally transformed the digital landscape, revolutionizing how organizations leverage technology for their operations and service delivery. This comprehensive article examines the evolution, current state, and future trajectory of cloud computing, exploring its core service models, deployment approaches, and enabling technologies. It investigates the vital role of virtualization, distributed systems, advanced networking, and automation tools in supporting cloud infrastructure. The article evaluates the significant benefits of cloud adoption, including enhanced scalability, cost optimization, improved accessibility, and accelerated innovation, while also addressing critical challenges such as security concerns, performance issues, regulatory compliance, and vendor lock-in. It explores practical applications across healthcare, education, financial services, and government sectors, demonstrating cloud computing's versatility and transformative impact. Furthermore, the article analyzes emerging trends, including edge computing, artificial intelligence integration, sustainability initiatives, and quantum computing developments, providing insights into the future direction of cloud technologies and their implications for digital transformation.